Design and development of mini wind tunnel for replicate airplane / Alisa Syafiqa Jasmi - Jasmi, Alisa Syafiqa (2022)
Wind tunnel is a tool used in aerodynamic research to study the effects of wind moving over the solid object. Present study, low velocity wind tunnel was designed and fabricated to reduce the drag and lift forces. A typical open circuit wind tunnel consists of motor and fan unit, settling chamber, contraction cone, test section and diffuser. The main work of the wind tunnel is to improve the design according to the aerodynamic shapes. Inside test section the wind velocity was measured about 36 m/s and pressure 36 bar. A replicate aeroplane model was placed parallel to the wind flow direction, velocity and pressure was measured. This mini wind tunnel is made for experiment purpose as we will see and learn how the flow of air through airplane. But this project, we will used mist/fog instead of air and also replicate airplane will be used. The objective are to understand the important aspect of designing and fabricate mini wind tunnel and designing and fabricating a mini wind tunnel for airplane model. For the scope of study are develop mini wind tunnel to represent real size wind tunnel condition and to design, fabricate and evaluate wind tunnel performance. Also, for the outcome, we will see how the air is flow through an airplane but for this study, we use mist instead of smoke and a replicate airplane.